1989
DOI: 10.1002/mrc.1260270116
|View full text |Cite
|
Sign up to set email alerts
|

14N NMR nuclear shielding and the electronic structure of dibenzo[1,3a,4,6a]tetrazapentalene

Abstract: "N NMR data and semiempirical molecular orbital calculations are reported for dibenzo-[1,3a,4,6a]tetrazapentalene (1). The "N signals were assigned by means of the results of the molecular orbital calculations and measured relative signal widths. A comparison was made with results for some azolopyridines. A linear correlation was obtained between the nitrogen shieldings, expressed with respect to the bridging nitrogen atom, and the corresponding relative charge densities. Thus nitrogen nuclear shielding result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

1990
1990
2003
2003

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 7 publications
1
5
0
Order By: Relevance
“…These are represented by the least-squares fitted values of the a term in Eq. [1] as reported triazines, and 1,2,4,5-tetrazine (1)(2)(3)(4)(5)(6)(7)(8). This is also in accord with analogous effects found in other molecular systems where in Table 3.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…These are represented by the least-squares fitted values of the a term in Eq. [1] as reported triazines, and 1,2,4,5-tetrazine (1)(2)(3)(4)(5)(6)(7)(8). This is also in accord with analogous effects found in other molecular systems where in Table 3.…”
Section: Resultssupporting
confidence: 90%
“…We have already shown that the a terms obtained for pyridinetype nitrogen shieldings of azine heteroaromatics (6-8) and for triazole ring systems (3) provide a sensitive probe for relative affinities of these nitrogens as acceptors of hydrogen bonds; the latter affinities may be termed an exhibition of variations in ''soft'' basicity, while analogous affinities with respect to a complete proton transfer should then be termed ''hard'' basicity. We have also found indications that the affinity of the nitrogen atoms concerned to accepting hydrogen bonds from solvent molecules, measured by the a terms for the relevant nitrogen shieldings, parallels that with respect to gas-phase protonation, as reckoned from ab initio calculated protonation energies (3,(6)(7)(8). The tetrazole systems examined in the present work should provide a rigorous test for such a correlation, in view of the fact that each contains three nonequivalent pyridine-type nitrogen atoms which can enter com- petition with respect to hydrogen bond or proton acceptance.…”
Section: Resultsmentioning
confidence: 93%
“…The latter can be justified by the fact that the two sets of experiments were performed in solvents of quite different polarity. However, the 14,15 N shielding of the azine N-oxides is slightly less sensitive to solvent effects than the 14,15 N shielding of azines, given that the direct interaction of the solvent molecules with the lone pair is now replaced by the direct interaction with the O atom. , …”
Section: Resultsmentioning
confidence: 98%
“…[27][28][29] Very pure and dry solvents were used in the NMR measurements as reported previously. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] The solutions were prepared and handled under a dry argon atmosphere in glove bags. The 14 N shielding measurements were taken on a Bruker AM500 Spectrometer at 35 + 0.2 ЊC, as maintained by a variable temperature unit, at a frequency of 36.14 MHz.…”
Section: Methodsmentioning
confidence: 99%